Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0210016
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation for treatment of recurrent C. difficile infection: An updated randomized controlled trial meta-analysis

Abstract: ObjectivesAlthough systematic evaluation has confirmed the efficacy of fresh fecal microbiota transplantation (FMT) for treatment of recurrent and/or refractory and/or relapse C. difficile infection (RCDI), it lacks the support of well-designed randomized controlled trials (RCTs), and the latest guidelines do not optimize the management of FMT. In this paper, we focus on an in-depth study of fresh FMT and fecal infusion times to guide clinical practice.MethodsWe reviewed studies in PubMed, Medline, Embase, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 57 publications
(67 reference statements)
2
98
0
1
Order By: Relevance
“…It is not clear whether fresh or frozen-thawed microbiota improves the efficiency of FMT; however, frozen-thawed microbiota is a more convenient method (36,37). Hamilton et al (38) reported the successful use of standardized, partially purified and frozen fecal microbiota to treat C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether fresh or frozen-thawed microbiota improves the efficiency of FMT; however, frozen-thawed microbiota is a more convenient method (36,37). Hamilton et al (38) reported the successful use of standardized, partially purified and frozen fecal microbiota to treat C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…The number of concurrent infections required to conduct fecal transplantations has not been clearly defined. However, recent evidence includes cases of patients with three or more incidents of CDI despite appropriate treatment, or two or more incidents of CDI with hospitalization and significant morbidity, patients with moderate CDI irresponsive to treatment with oral vancomycin for over a week, or patients with severe CDI irresponsive to oral vancomycin for 48 hours [110][111][112]. In a randomized study, 93% of the patients that received oral vancomycin and bowel irrigation followed by FMT exhibited a significant decrease in their diarrheal episodes, whereas only 31% of the patients that received only vancomycin and 23% of those who received vancomycin and bowel irrigation had positive outcomes, demonstrating that FMT was significantly more effective for the treatment of recurrent C. difficile infection than the use of vancomycin [113].…”
Section: Restoration Of the Gut Microbiota As Therapeutic For CDImentioning
confidence: 99%
“…Second, the effect of pre‐procedural PPIs on multiple infusion FMT was not studied. Numerous trials have shown impressive efficacy of FMT with multiple infusions, approaching 93–100% . For this review, we defined our inclusion criteria to include only first infusion data to allow for comparison of the primary and secondary endpoints and minimize confounding factors.…”
Section: Discussionmentioning
confidence: 81%